Mirror foot : a case report of rare ten toes polydactyly - Sitorus, Gina Yunit J; Putra, Teuku Nanda; Ikhsan, Muhammad; Jannah, Siti Miftahul (Surgical Residency Program Syiah Kuala University, 2024)
Background: A rare congenital abnormality known as